Evaluation Of Dual Colours Illumination For Particle Image Velocimetry Measurement - Chew, Tian Feng (Universiti Sains Malaysia, 2017)
In past decades, particle image velocimetry (PIV) has been widely used in measuring fluid flow and a lot of researches have been done to improve the PIV technique. The purpose of this research project is to evaluate the capability of dual colours high power light emitting diodes (HPLED) illumination to replace traditional PIV. Dual colours HPLEDs PIV can apply single frame double pulses which provides direction or velocity vector of the particles. The idea of dual colours PIV directly replaces lasers as illumination system and high speed camera as recording system, as a single frame can be captured by a normal camera. An illumination system is designed and fabricated to perform fluid flow analysis. The results of the experiment is promising and the feasibility of dual colours PIV is ensured.